Lactoferrin Reduces Necrotizing Enterocolitis Severity by Upregulating Intestinal Epithelial Proliferation - Liu, Jia; Zhu, Haitao; Li, Bo; Robinson, Shaiya C.; Lee, Carol; O'Connell, Joshua S.; Bindi, Edoardo; Zheng, Shan; Sherman, Philip M.; Pierro, Agostino (European Journal of Pediatric Surgery, 2020)
Introduction Necrotizing enterocolitis (NEC) is a devastating intestinal illness in premature infants characterized by severe intestinal inflammation. Despite medical interventions, NEC mortality remains alarmingly high, which necessitates improved therapies. Lactoferrin is among the most abundant proteins in human milk and has important immunomodulatory functions. While previous studies have indicated protective effects of lactoferrin against neonatal sepsis and NEC, the underlying mechanism remains unclear. We hypothesize that lactoferrin downregulates inflammation and upregulates proliferation in intestinal epithelium during NEC injury.Materials and Methods NEC was induced by hypoxia, gavage feeding of hyperosmolar formula and lipopolysaccharide between postnatal day P5 and P9 (n = 8). Breastfed mice were used as control (n = 7). Lactoferrin (0.3 g/kg/day) was administered once daily by gavage from P6 to P8 in both NEC (NEC + Lac; n = 9) and control mice (Cont + Lac; n = 5). Distal ileum was harvested on P9 and analyzed for disease severity, inflammation, and proliferation. Groups were compared using one-way ANOVA and t-test appropriately; p < 0.05 was considered significant.Results Compared to NEC group, lactoferrin-treated NEC mice had reduced disease severity, reduced inflammation markers IL-6 and TNF-α expression and increased intestinal stem cell marker Lgr5 + expression. Lactoferrin-treated NEC mice exhibited increased nuclear β-catenin, indicating upregulated Wnt pathway, and increased Ki67 positivity, suggesting enhanced proliferation. Furthermore, lactoferrin administration to control mice did not affect intestinal inflammation as well as Lgr5 + stem cell expression and epithelial proliferation. This supports the safety of lactoferrin administration and indicates that the beneficial effects of lactoferrin are present when intestinal injury such as NEC is present.Conclusion Lactoferrin administration reduces the intestinal injury in experimental NEC by downregulating inflammation and upregulating cell proliferation. This beneficial effect of lactoferrin in stimulating cell proliferation is mediated by the Wnt pathway. This experimental study provides insights on the mechanism of action of lactoferrin in NEC and the role of lactoferrin in enteral feeding.
Keywords: lactoferrin; necrotizing enterocolitis; inflammation; proliferation; Wnt pathway